Awareness of influenza and pneumococcal vaccines in diabetic patients - Sözen, Mehmet (J Diabetes Metab Disord, 2021)
PURPOSE: In our study, it was aimed to evaluate the awareness of diabetic patients about vaccination status and vaccines. METHODS: This cross-sectional study was conducted between January 2019 and February 2019. A survey questioning the level of knowledge about and vaccination status for influenza and pneumonia vaccines was applied by face-to-face interviews with patients with diabetes mellitus who admitted to the diabetes outpatient clinic. All results were evaluated with SPSS-20.0. RESULTS: A total of 202 patients [66 male (32.7%) and 136 female (67.3%) patients; with a mean age of 57.7 ± 11.3 years and mean duration of diabetes 10.7 ± 7.9 years] were recruited in the study. Majority of the patients (92.6%) were type 2 DM patients. 59.4% of the patients had never been vaccinated. The rate of those who had pneumonia vaccine was very low, only 14.7%. The vast majority of the patients had knowledge about vaccines and their most common source of information was nurses. 53% of patients believed that diabetic patients should be vaccinated regularly. 16.8% of the patients were reluctant to have the recommended vaccine. The factor with greatest impact on this was that they did not consider the vaccine necessary. 52.5% of the patients recommended to be vaccinated had the recommended vaccine. 26.4% of the patients who were not enthusiastic about the recommended vaccine had pneumococcal vaccine after being informed about the vaccine. CONCLUSION: It was observed that the information given about vaccines positively affected the vaccination rate. The main barrier to vaccination was the lack of information about the need for influenza vaccination. Designing strategies and training programs for healthcare professionals and patients should be the main goal to improve vaccination coverage and vaccination rates.